A Digitalisasi Produk Ekonomi Kreatif: Upaya Membangun Wirausaha Inovatif di Masa dan Pasca Pandemi Covid 19 Bagi Masyarakat Desa Alale Kabupaten Bone Bolango - Nurwan; Resmawan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has speared almost all country in the world, including Indonesia. The impact of the Covid-19 pandemic in various aspects of life, including economic problems. Some small and medium industries suffered a lot, but not a few are taking advantage of these situations to gain profits through creativity and digital innovation. In response to the existing conditions, efforts to assist the community of small and medium business actors and other community groups to digitize the creative economy in order to develop innovative entrepreneurs. The aim of this activity is to provide solutions for business groups and the general public to improve the economy during pandemic and post the Covid-19 pandemic. The form of activity in this service is training on the use of information technology (social media) in supporting creative economic activities such as product design, digital marketing and building business networks.